The Roles of Intracellular Chaperone Proteins, Sigma Receptors, in Parkinson’s Disease (PD) and Major Depressive Disorder (MDD) - Yang, Kai; Wang, Changcai; Sun, Taolei (Frontiers in Pharmacology, 2019)
Sigma receptors, including Sigma-1 receptors and Sigma-2 receptors, are highly expressed in the CNS. They are intracellular chaperone proteins. Sigma-1 receptors localize mainly at the mitochondria-associated endoplasmic reticulum (ER) membrane (MAM). Upon stimulation, they translocate from MAM to plasma membrane (PM) and nucleus, where they interact with many proteins and ion channels. Sigma-1 receptor could interact with itself to form oligomers, its oligomerization states affect its ability to interact with client proteins including ion channels and BiP. Sigma-1 receptor shows high affinity for many unrelated and structurally diverse ligands, but the mechanism for this diverse drug receptor interaction remains unknown. Sigma-1 receptors also directly bind many proteins including G protein-coupled receptors (GPCRs) and ion channels. In recent years, significant progress has been made in our understanding of roles of the Sigma-1 receptors in normal and pathological conditions, but more studies are still required for the Sigma-2 receptors. The physiological roles of Sigma-1 receptors in the CNS are discussed. They can modulate the activity of many ion channels including voltage-dependent ion channels including Ca2+, Na+, K+ channels and NMDAR, thus affecting neuronal excitability and synaptic activity. They are also involved in synaptic plasticity and learning and memory. Moreover, the activation of Sigma receptors protects neurons from death via the modulation of ER stress, neuroinflammation, and Ca2+ homeostasis. Evidences about the involvement of Sigma-1 receptors in Parkinson’s disease (PD) and Major Depressive Disorder (MDD) are also presented, indicating Sigma-1 receptors might be promising targets for pharmacologically treating PD and MDD.